1971
DOI: 10.1002/polc.5070360106
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative reactions of cellulose initiated by free radicals

Abstract: Oxidative reactions in cellulose are commonly initiated by thermal, ultraviolet, and high‐energy radiations and by chemical oxidation. Long‐lived free radicals, formed in cellulose on the localization of energy from thermal, ultraviolet, and high‐energy radiations, and short‐lived free radicals, formed in cellulose by oxidation, e.g., by ceric ion or redox reactions, were investigated by electron spin resonance spectroscopy. Dehydrogenation and oxidative depolymerization reactions of cellulose are indicated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This type of reaction cannot account for the allyl radicals in AIBNinitiated samples, since the radiation of 3600 J\. The low spin density on the central carbon atom, together with the large line widths, prevents the methyl protons in radical (4,70) from showing resolved hyerfine splittings. In this case allyl radicals are probably formed by attack of another radical at a terminal double bond of a dead chain (4.75).…”
Section: Photosensitized By Azo-compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of reaction cannot account for the allyl radicals in AIBNinitiated samples, since the radiation of 3600 J\. The low spin density on the central carbon atom, together with the large line widths, prevents the methyl protons in radical (4,70) from showing resolved hyerfine splittings. In this case allyl radicals are probably formed by attack of another radical at a terminal double bond of a dead chain (4.75).…”
Section: Photosensitized By Azo-compoundsmentioning
confidence: 99%
“…70. Change in ESR spectra of UV-irradiated at 77 K of polyurethane with increasing of temperature l673 )…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of the use of ESR in studying the structure of free radicals in cellulose and its derivatives initiated by ionizing radiation, light, heat, oxidation-reduction systems, and mechanical action were published by Arthur [11][12][13]. In these past years, it has been also well established that lineshape and width and hyperfine splitting constants of ESR spectra of γ -and UV-irradiated cellulose depend on the type of cellulose and are specific for the type of irradiation [14], providing a wide characterization of free radical species generated under electromagnetic irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Even though cellulose and starch have similar chemical formulas, their radical formation process may differ due to their structures (Rånby, 1977). It has been reported that the triplet ESR spectrum of cellulose (pure cotton) is due to the equal interaction of the two hydrogen atoms at the C6 position with the unpaired electron formed by the removal of the hydrogen atom at the C5 position of the glucose unit (Rånby, 1977;Arthur, 1971;Arthur & Hinojosa, 1971;Arthur et al, 1966;Baugh et al, 1967) (see Fig. 1 B).…”
Section: Appearance and Disappearance Of The Esr Signalsmentioning
confidence: 99%